District Residency Program: Exploration of the Perceptions of Postgraduates -A Way Ahead - Sindhu Abhivanth R; Suwarna Madhukumar (RGUHS Journal of Medical Sciences)
Background The District Residency Program DRP introduced by the National Medical Council NMC in 2020 mandates a three-month posting for second-year postgraduate students in primary or secondary healthcare centers. Designed as a learning while serving initiative the program faces several challenges including both residents and authorities. This study evaluated its benefits challenges and limitations.Objectives The objectives of this study were to assess perceived benefits barriers and challenges faced by residents during DRP to identify limitations and to recommend sustainable improvements.Methods A cross-sectional study was conducted among 57 residents of MVJ Medical College amp Research Hoskote Bengaluru who completed the DRP. Data was collected using a validated self-prepared questionnaire.Results Approximately 98.2 of postgraduates were aware of DRP but only 10.5 attended more than 80 OPD patients daily. Most residents reported improvements in knowledge 56.1 skills implementation 84 hands-on learning 78.9 and treatment 70.2 with 86 feeling they significantly contributed to the assigned health facility. They received guidance supervision and positive teamwork from PHCCHC staff. However challenges related to transport accommodation food and security were major deterrents to their participation.Conclusion DRP largely meets its intended objectives enhancing clinical skills and knowledge of local diseases. However poor amenities and the lack of specialty care in primary health centers PHCsCommunity health centers CHCs remain key concerns.